2012
DOI: 10.1074/jbc.m112.411827
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of Cancer Cell Heterogeneity in Caspase-dependent Apoptosis Subsequent to Mitochondrial Outer Membrane Permeabilization

Abstract: Background: Computational systems models may allow understanding of progression and impairment of apoptosis based on quantitative protein profiles. Results: We found apoptosis to be impaired in some cell lines after MOMP, which can be understood by our systems model "APOPTO-CELL". Conclusion: APOPTO-CELL helps to understand heterogeneity in apoptosis execution after MOMP. Significance: APOPTO-CELL may help to assess cancer-specific efficacy of chemotherapeutics that induce apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…In this step, caspase-3 is activated either by a positive feedback loop with upstream caspase-8 (socalled type I cells) or after MOMP which is mediated by of the BCL-2 protein BID (type II cells). We further note that MOMP induces an energetic crisis caused by the loss of cytochromec, which may lead to necrosis or metabolic impairment when caspase-dependent apoptosis is blocked [21,30,31].…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedmentioning
confidence: 81%
See 3 more Smart Citations
“…In this step, caspase-3 is activated either by a positive feedback loop with upstream caspase-8 (socalled type I cells) or after MOMP which is mediated by of the BCL-2 protein BID (type II cells). We further note that MOMP induces an energetic crisis caused by the loss of cytochromec, which may lead to necrosis or metabolic impairment when caspase-dependent apoptosis is blocked [21,30,31].…”
Section: Pathways Of Cardiomyocyte Apoptosis Relevant To Dox -Inducedmentioning
confidence: 81%
“…Indeed, with such quantitative signal transduction models, we were previously able to predict patient specific susceptibility to chemotherapy [31,44,54,84,85]. It is therefore expected that these models in combination with biomolecular studies that investigate molecular mediators of apoptosis can further help to identify patient more vulnerable to DOX-induced cardiac apoptosis and DCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, caspase-9 activation and apoptosis execution is highly efficient in these cells. Similar unfavorable ratios for a dimerization-based activation process were reported in various other cell lines, including MCF-7 breast cancer cells, human colon carcinoma cell lines (HCT-116, Lovo, DLD-1, HT29), and panels of 11 glioblastoma and 11 melanoma cell lines (39,40,59). Structural analysis based on electron cryo-microscopy data indicated that the seven Apaf-1 CARD domains may form a flexible procaspase-9 recruitment platform in the center of the apoptosome complex (60).…”
Section: Systems-based Evidence For Allosteric Caspase-9 Activationmentioning
confidence: 73%